O sucesso da invasora Urochloa arrecta em diferentes contextos e seus impactos em um reservatório. - Teixeira, Mariana Carolina (2015)
Biological invasions threat all kinds of ecosystems because they can alter their structure and functioning in ways that are negative to their integrity. In freshwater environments, aquatic macrophytes are common invaders and tend to impact physical and chemical characteristics of water and sediments, as well as macrophyte-dwelling fauna. Urochloa arrecta (Poaceae) is a highly invasive macrophyte that has been colonizing lakes, Rivers, streams and reservoirs in many regions of South America. Many factors interact to determine whether a species will succeed as an invader or not in a community. According to theories in invasion ecology, native communities are able to pose resistance to the establishment of invasive species through biotic interactions. For aquatic macrophytes, competition for nutrients between the native community and invasive species could result in disadvantages for the invaders, mining their establishment. Such interaction and its result depend, however, on the environment where they take place, being regulated by nutrient availability. Excessive input of nutrients is common in freshwaters and can interfere in the interaction between native communities and invasive species, helping to determine if the community will be able to resist the invasion or not. We experimentally tested the interaction between nutrient enrichment and biotic resistance in the establishment success of Urochloa arrecta. We observed that nutrient enrichment and biotic resistance interactively affect U. arrecta?s success, reinforcing the idea that factors that influence invasions are context-dependent. Spatial distribution of nutrients in the substrate may also interfere in the competitive interaction between a native community and an invader. In a second experiment, we tested differences between the success of U. arrecta when introduced in native communities in mesocosms with homogeneous or heterogeneous distribution of nutrients in the sediment. We observed that spatial distribution of nutrients had no effect on U. arrecta?s success, but nutrient addition provided native community with better resistance to invasion. We also investigated, with field observations, if sites where U. arrecta was dominant differed from sites where a native species was dominant and from sites with no aquatic vegetation in terms of physical and chemical characteristics of water. Electrical conductivity and pH did not differ among invader-dominated, native-dominated and unvegetaded sites. Underwater radiation was higher in unvegetaded sites than in both native and invader-dominated sites. Dissolved oxygen was significantly lower in invader-dominated sites in comparison with both native-dominated and unvegetaded sites. In conclusion, we found that biotic resistance is important to prevent the establishment of U. arrecta, especially in interaction with nutrient enrichment, and that this species can alter the quality of shore habitats by lowering dissolved oxygen concentrations within its mats.